STUDI PERBANDINGAN DI INDONESIA DAN MALAYSIA MENGENAI UPAYA HUKUM WARGA NEGARA ASING YANG DIDEPORTASI : Comparative Study in Indonesia and Malaysia on Legal Remedies for Deported Foreign Nationals - Shafa Shafira Putriana; Tri Sulistyowati (Faculty of Law, Universitas Trisakti, 2026)
Deportation is the forced removal or repatriation of a person, particularly a foreign national, from the territory of one country to their country of origin or another location. When deportation is imposed, foreign nationals are often in a very vulnerable position because the decision is unilateral, swift, and has serious consequences for their lives. The research question in this study is how foreign nationals can use legal mechanisms to challenge deportation in Indonesia and Malaysia. The research method uses a normative approach, analyzing legislation and relevant legal literature to explore systemic comparisons between the two jurisdictions. The results of the study show that Indonesia treats deportation as an administrative action that can be challenged through internal appeals or review in administrative courts, while Malaysia tends to provide more limited space with strong executive discretion. The analysis reveals significant differences in the patterns of protection for foreign nationals, particularly regarding access to objection mechanisms. This study concludes that harmonization between state security and procedural rights protection is a crucial aspect that needs to be strengthened in both countries.